1969
DOI: 10.1002/art.1780120206
|View full text |Cite
|
Sign up to set email alerts
|

Synovial collagenase: Its presence in culture from joint disease of diverse etiology

Abstract: Closed needle biopsy of synovium from inflamed joints yields enough tissue to detect production and/or release of collagenase from these tissues. Collagenase activity was found in synovium from 8 of 8 patients with probable rheumatoid arthritis, in 6 of 9 patients with nonrheumatoid inflammatory synovitis, and in 1 of 6 patients with degenerative joint disease. One of 2 patients with classic rheumatoid arthritis had activity in synovium regrown after synovectomy. Therefore synovial collagenase is not unique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…Historically, the serinedependent enzymes have been known about longer than have the MMPs, which rapidly became in vogue following their discovery. Indeed, arthritis was the first disease to be associated with an MMP, when a collagenase was detected in diseased synovium (3). The serine proteinases are perhaps better known as enzymes used in medicine (for review, see ref.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the serinedependent enzymes have been known about longer than have the MMPs, which rapidly became in vogue following their discovery. Indeed, arthritis was the first disease to be associated with an MMP, when a collagenase was detected in diseased synovium (3). The serine proteinases are perhaps better known as enzymes used in medicine (for review, see ref.…”
Section: Introductionmentioning
confidence: 99%
“…Other morphologic and histochemical studies of rheumatoid joints have revealed evidence of erosions and collagen lysis within superficial zones of cartilage distal to pannus, suggesting that mechanisms other than synovial pannus invasion contribute to cartilage attenuation in RA (7). Neutrophils are frequently found in abundance in rheumatoid joint effusions and contain within their subcellular granules enzymes capable of degrading proteoglycan and collagen constituents of articular cartilage (8,9).…”
mentioning
confidence: 99%
“…Early hopes that synovial collagenase might be specific for rheumatoid arthritis were dashed when the enzyme was found in synovial biopsies taken from patients with synovitis of many diverse origins (25). However the intensity and chronicity of the rheumatoid process seem to be directly proportional to the amounts of collagenase released from primary cultures of rheumatoid synovium (26).…”
mentioning
confidence: 99%